Restoring labor market functions to address job insecurity among middle-aged and older workers - Joseph Han (Korea Development Institute (KDI), 2024)
In the Republic of Korea, middle-aged and older workers experience unusually high job insecurity due to limited labor demand for them. To address this issue, labor market policies and practices must be reformed to make it easier for firms to hire these workers as regular employees. Instead of imposing regulatory mandates, it is crucial to enhance the functioning of labor markets to reduce involuntary early retirements among older workers and prevent career disruptions for middle-aged women. These reforms will also facilitate the gradual extension of the mandatory retirement age, a necessary step in light of Korea's rapidly aging population.
Keywords: 330